Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/cplu.201402131
|View full text |Cite
|
Sign up to set email alerts
|

Diethyl Tartrate Linked Chiral Macrocyclic Manganese(III)–Salen Complex for Enantioselective Epoxidation of Olefins and Oxidative Kinetic Resolution of Racemic Secondary Alcohols

Abstract: A diethyl tartrate linked chiral macrocyclic manganese(III)–salen (salen=N,N′‐ethylenebis(salicylimine)) complex has been used for the enantioselective epoxidation of nonfunctionalized alkenes, namely, indene and chromenes, as well as oxidative kinetic resolution of racemic alcohols. For the epoxidation reaction, a 2.5 mol % catalyst loading in the presence of pyridine N‐oxide as an axial ligand and urea–H2O2 adduct as an oxidant gave respective epoxides in high yield (>97 %) and enantiomeric excess (ee, up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Kinetic measurements revealed first-order dependence of the reaction rate on the catalyst concentration . Later, several macrocyclic manganese complexes (bearing two Mn centers) were prepared and tested as catalysts in the epoxidations with urea hydroperoxide, using pyridine N -oxide as the additive. , The authors demonstrated that organic carbonates (such as dimethyl carbonate and propylene carbonate) could be used as reaction media for the manganese salen-catalyzed epoxidations with urea hydroperoxide; the resulting protocol, however, required as much as 5 mol % catalyst loadings . Tomaselli and Sfazzetto conducted the epoxidations with H 2 O 2 (8 equiv vs olefin) in aqueous media, in the presence of diethyltetradecylamine N -oxide: the latter was believed to act both as a surfactant and as a cocatalyst …”
Section: Asymmetric Epoxidation Reactionsmentioning
confidence: 99%
“…Kinetic measurements revealed first-order dependence of the reaction rate on the catalyst concentration . Later, several macrocyclic manganese complexes (bearing two Mn centers) were prepared and tested as catalysts in the epoxidations with urea hydroperoxide, using pyridine N -oxide as the additive. , The authors demonstrated that organic carbonates (such as dimethyl carbonate and propylene carbonate) could be used as reaction media for the manganese salen-catalyzed epoxidations with urea hydroperoxide; the resulting protocol, however, required as much as 5 mol % catalyst loadings . Tomaselli and Sfazzetto conducted the epoxidations with H 2 O 2 (8 equiv vs olefin) in aqueous media, in the presence of diethyltetradecylamine N -oxide: the latter was believed to act both as a surfactant and as a cocatalyst …”
Section: Asymmetric Epoxidation Reactionsmentioning
confidence: 99%
“…Moreover, multigram‐scale catalysis was achieved with no loss of performance suggesting the scalable character of this reaction. The performance of diethyl tartrate linked chiral Mn‐salen complexes in the enantioselective epoxidation of olefins and in the oxidative kinetic resolution of racemic secondary alcohols was also studied with very good results in both cases . Recently, the enantioselective hydrophosphonylation of N ‐benzyl imines and isatin‐derived ketimines was also described by in situ generated macrocyclic Ti‐salen complexes .…”
Section: Macrocyclic Salen Complexesmentioning
confidence: 99%
“…The performance of diethyl tartrate linked chiral Mn-salen complexes in the enantioselective epoxidation of olefins and in the oxidative kinetic resolution of racemic secondary alcohols was also studied with very good results in both cases. [61] Recently, the enantioselective hydrophosphonylation of N-benzyl imines and isatin-derived ketimines was also described by in situ generated macrocyclic Ti-salen complexes. [62] Here, the catalyst with the flexible longer ethyleneglycol linker showed best results in term of yield (up to 92 %) and selectivity (up to 98 % ee) compared to other shorter or more rigid links, indicating the important role of flexibility in the enantioselective catalytic environment.…”
Section: Macrocyclic Salen Complexesmentioning
confidence: 99%
“…Later a series of macrocyclic diethyl tartrate linked Mn(III) salen complexes were synthesized and utilized for asymmetric epoxidation of olefins. Catalyst 10 (Figure ) showed promising results for asymmetric epoxidation of olefins, and therefore, it was studied for OKR of racemic secondary alcohols . The effect of catalyst loading and solvent was examined for asymmetric oxidative kinetic resolution of racemic 1‐phenylethanol.…”
Section: Chiral Mn(iii) Salen Complexes For Okr Of Racemic Secondary mentioning
confidence: 99%
“…Catalyst 10 ( Figure 3) showed promising results for asymmetric epoxidation of olefins, and therefore, it was studied for OKR of racemic secondary alcohols. 64 The effect of catalyst loading and solvent was examined for asymmetric oxidative kinetic resolution of racemic 1-phenylethanol. The result revealed that on substrate 1-phenylethanol, the best enantioselectivity (95%) and conversion (66%) rating was observed when the catalyst loading was 1.5 mol% (Table 2).…”
Section: Recyclable Chiral Mn(iii) Salen Complexesmentioning
confidence: 99%